Mexican-heritage fathers’ impact on their children’s math development: a mini review - Becerra Songolo, Rogelio (Frontiers in Education, 2026)
Literature on fathers’ characteristics and parenting behaviors that influence math development remains limited, particularly with respect to Mexican-heritage (MH) fathers. Thus, this mini review addresses this gap by discussing seminal work and recent findings that can point future research in useful directions. The review relies on an established heuristic model that places fathers’ multidimensional qualities as important contributors to children’s development. Importantly, this mini review is among the first to apply this framework specifically to the study of MH fathers in relation to early math development. Twelve peer-reviewed articles published as early as 2000, which analyzed at least a sub-sample of MH or Latine fathers’ characteristics and parenting behaviors were included in this mini review. The review examines paternal characteristics like beliefs about gender roles, linguistic, educational, and financial resources, as well as parenting behaviors such as paternal engagement, responsiveness, and early investments in education. Drawing from studies of diverse methodological approaches, this non-exhaustive review illustrates the varied ways in which fathering and math development have been conceptualized among MH populations. Yet, mixed methods analyses– especially those that focus on non-heterosexual MH fathers– could highlight developmental supports among samples seldom studied. The review concludes by discussing the ethical and educational implications of a continued focus on MH children’s math development. Given the large proportion of MH children in US classrooms and the need to enhance math education through culturally responsive manners, it is imperative to continue to focus on father-child dynamics within this demographic.